2012
DOI: 10.1002/anie.201109084
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Vapor Sorption of Xylenes: Prioritized Selectivity as a Means of Separating All Three Isomers Using a Single Substrate

Abstract: A Werner complex is highly selective for o-xylene in a vapor mixture containing all three isomers. However, in the absence of o-xylene, the substrate shows similar selectivity for m-xylene over p-xylene. Kinetic studies show a different trend whereby m-xylene is absorbed most rapidly, implying that thermodynamic factors must be responsible for the selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
130
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(133 citation statements)
references
References 22 publications
3
130
0
Order By: Relevance
“…The most promising separation method for these molecules has been shown to be enclathration, however isomer recovery usually leads to byproduct formation 11. In this regard, Barbour and Lusi have recently shown that a single Ni‐based clathrate may be used to neatly separate the xylene isomers in the vapor phase 12…”
Section: Summary Of the Competition Experiments Using Llip And Ullip mentioning
confidence: 95%
See 1 more Smart Citation
“…The most promising separation method for these molecules has been shown to be enclathration, however isomer recovery usually leads to byproduct formation 11. In this regard, Barbour and Lusi have recently shown that a single Ni‐based clathrate may be used to neatly separate the xylene isomers in the vapor phase 12…”
Section: Summary Of the Competition Experiments Using Llip And Ullip mentioning
confidence: 95%
“…This 10 % extraction ability, that is, one molecule per C 60 per cycle, is comparable to other separation approaches 1d. 2b, 6, 12, 22…”
Section: Summary Of the Competition Experiments Using Llip And Ullip mentioning
confidence: 99%
“…In molecular crystals, intricate equilibria are known to exist between the pure compounds and their hydrogen-bonded water and alcohol solvates (Braga et al, 2008;Braun et al, 2012). Similarly, ammonia and hydrohalic acids can reversibly coordinate to metals in discrete (Mínguez Espallargas et al, 2007) and polymeric complexes (Adams et al, 2007), while clathration of aromatic species can be driven by the increased lattice energy deriving from weak van der Waals interactions (Lusi & Barbour, 2012). Even the simple selective exposure of a given crystallographic face to water vapour can trigger molecular reorientation (Jiang et al, 2013).…”
Section: Topochemical Control In Desolvation Of Coordination Polymersmentioning
confidence: 99%
“…Xylene isomers separation has attracted highly attention over the world as a result of similar physicochemical properties of these isomers. Various methods for Xylene separation have been applied such as distillation [1], fractional crystallization [2] and adsorption [3]. The latest method has been most used as alternatives in industrial process for the separation [4].…”
Section: Introductionmentioning
confidence: 99%